1991
DOI: 10.1042/bj2760163
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between inositol tris- and tetrakis-phosphates. Effects on intracellular Ca2+ mobilization in SH-SY5Y cells

Abstract: The potential Ca2(+)-releasing activity of the inositol tetrakisphosphates Ins(1,3,4,6)P4 and DL-Ins(1,4,5,6)P4 and the inositol pentakisphosphate Ins(1,3,4,5,6)P5 and their effect on Ins(1,4,5)P3- and DL-Ins (1,3,4,5)P4-mediated Ca2+ release were examined in permeabilized SH-SY5Y human neuroblastoma cells. Neither DL-Ins(1,4,5,6)P4 nor Ins(1,3,4,5,6)P5 exhibit Ca2(+)-releasing activity at concentrations up to 10 microM, but Ins(1,3,4,6)P4 releases Ca2+ dose-dependently, with an EC50 value (conen, giving half-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
1

Year Published

1993
1993
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 27 publications
4
38
1
Order By: Relevance
“…By moving our experimental protocols more closely towards those used by Bird et al [6] amplification of the response to a submaximal Ins(2,4,5)P $ dose by InsP % at 1 % of that of Ins(2,4,5)P $ ; see Figure 8], that are difficult to account for by metabolic effects such as protection of InsP $ against hydrolysis. These data, in common with previous data from lacrimal cells and with data from other systems that show a clear response to InsP % [10][11][12][13], indicate that, in all cases, more Ca# + may be mobilized by Ins(1,4,5)P $ when InsP % is also present. Although the original interpretation of this response in lacrimal cells emphasized the effect of InsP % on InsP $ -induced Ca# + entry [3], subsequent data [4,5,7], including those obtained in the present study, have indicated that this is more likely to be an indirect consequence of increased Ca# + mobilization.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…By moving our experimental protocols more closely towards those used by Bird et al [6] amplification of the response to a submaximal Ins(2,4,5)P $ dose by InsP % at 1 % of that of Ins(2,4,5)P $ ; see Figure 8], that are difficult to account for by metabolic effects such as protection of InsP $ against hydrolysis. These data, in common with previous data from lacrimal cells and with data from other systems that show a clear response to InsP % [10][11][12][13], indicate that, in all cases, more Ca# + may be mobilized by Ins(1,4,5)P $ when InsP % is also present. Although the original interpretation of this response in lacrimal cells emphasized the effect of InsP % on InsP $ -induced Ca# + entry [3], subsequent data [4,5,7], including those obtained in the present study, have indicated that this is more likely to be an indirect consequence of increased Ca# + mobilization.…”
Section: Discussionsupporting
confidence: 89%
“…Despite further studies [7] that showed, by measuring the less Ca# + -sensitive Cl − current in addition to the Ca# + -dependent K + current, that InsP $ \InsP % synergism did occur at very high InsP $ concentrations, the differences between results from the two laboratories have remained unexplained. It may be in part because of this and other unresolved discrepancies [8,9] in the findings of these two laboratories that subsequent reports of InsP % -dependent modulation of InsP $ -induced Ca# + mobilization [10][11][12][13] have frequently been ignored [14].…”
Section: Inspmentioning
confidence: 99%
“…In the present study, we have identified binding sites for InsP4 with an affinity of approximately 3 nM at a concentration of 127 fmol mg-' protein in detergent-solubilized membranes prepared from canine colonic circular smooth muscle. Similar affinities for InsP4 were reported in cerebellum (Doine et al, 1990;Theibert et al, 1991 (Enyedi & Williams, 1988;Enyedi et al, 1989;Challiss et al, 1991 (Gawler et al, 1991). Using single cell voltage clamping methods, Morris et al (1987) have demonstrated that InsP4, in the presence of InsP3, evokes a sustained increase in Ca2+-activated K+ current which is dependent on external Ca2".…”
Section: Subcellular Fractionationsupporting
confidence: 63%
“…InsP4 has also been implicated in Ca2+ homeostasis. Proposals for the action of InsP4 have included activation of extracellular Ca2+ entry (Irvine & Moor, 1986;Changya et al, 1989), modulation of the InsP3-sensitive Ca2+ pool (Gawler et al, 1991), and a direct effect on intracellular Ca2+ mobilization (Hill et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, another class of inositol phosphates which includes Ins(1,3,4,6)P 4 , L-ch-Ins(2,3,5)PS 3 , and D-6-deoxy-myo-Ins(1,4,5)-PS 3 (3,23,24) have been shown to induce Ca 2ϩ release through the InsP 3 receptor, but are unable to release Ca 2ϩ to the same extent as seen with maximal concentrations of Ins(1,4,5)P 3 . These analogues have also been classified as partial agonists.…”
Section: Kinetics Of Insp 3 -Induced Ca 2ϩ Releasementioning
confidence: 99%